Some regularities of liquid-phase catalytic disproportionation of γ-trifluoropropylmethyldichlorosilane in ethyland phenylchlorosilanes presence - V. G. Lakhtin; M. I. Eremeeva; E. G. Gordeev; N. V. Ushakov; V. G. Bykovchenko; A. D. Kirilin; E. A. Chernyshev (Тонкие химические технологии, 2014)
γ-Trifluoropropylmethyldichlorosilane interaction with ethyl- and phenylchlorosilanes in aluminum chloride presence was studied. It is demonstrated that besides expected exchange reactions of Cl↔F at silicon, exchange reactions proceed with the participation of γ-trifluoropropyl substituent resulting in the formation of a few new unsaturated allyl-type compounds. There is no intermolecular exchange of organic substituents. It is found that chlorine atoms, which are in γ-position towards silicon in a hydrocarbon chain, are active in dehydrochlorination reactions in aluminum chloride presence in contrast to chlorine atoms in α- and β-positions.Tetraethylsilane has been found to be passive in the studied reactions in contrast to ethylchlorosilanes. A scheme explaining the obtained results is proposed, and quantum-chemical calculations of the basic reactions have been made.